FORMATION OF THE MECHANISM FOR ENSURING THE ECONOMIC SECURITY OF AN ENTERPRISE (Development Service Industry Management, 2025)
The article highlights and analyzes the issues of managing the economic security of enterprises and organizations. The purpose of the study is defined as the generalization of methodological and applied provisions for the formation of a mechanism to ensure the economic security of an enterprise. It is shown that the practical testing of the policy of ensuring the economic security of an enterprise presupposes the formation and implementation of the corresponding managerial mechanism as a comprehensive system of interconnected elements and specific measures to achieve the defined objectives. It has been proved that the introduction of such a mechanism requires the identification of its elements, subjects and objects, methods, tasks, technologies, organizational processes and regulations, and so on. It is determined that such a mechanism represents an integrated system of managerial actions for the development and implementation of strategic and tactical measures, ensuring the stability of the enterprise in a changing external environment. It is argued that the methodological approach to the formation of the mechanism for ensuring the economic security of an enterprise encompasses the development of a strategy, the formation of an action plan, and includes interconnected economic, organizational, institutional, technical, socio-psychological, and other instruments. The goal of the institutionalization of the mechanism for managing the economic security of an enterprise is defined as ensuring its sustainable functioning through the implementation of comprehensive measures aimed at protection from threats and risk management, as well as adaptation to changing conditions. It has been proved that the elements of the mechanism must take into account the specifics of the agrarian business, which is characterized by a high dependence on natural factors and seasonality. The expediency has been substantiated, and the characteristics have been provided for the organizational, financial, analytical, material, socio-psychological, legal, environmental, and innovation-technological components of the economic security of an enterprise.
Keywords: economics and enterprise management; enterprises; economic security; mechanism of ensuring; formation; management, strategic management; sustainability; viability; challenges; risk and threats